Análise energética e exergética de uma bomba de calor para desumidificação e aquecimento do ar - Maia, Nayana Lôbo (2014)
The heat pump is a refrigeration unit with several applications in commercial, industrial and residential sectors. The heat pump is basically constituted of five components: compressor, condenser, expansion device, evaporator and fan. A heat pump was developed herein for air dehumidification and heating at moderate temperatures for drying of thermosensitive products. A thermodynamic model was developed to study the heat pump, based on the Law of Conservation of Mass and First and Second Laws of Thermodynamics. Measurement instruments were installed to obtain the necessary experimental data for the energy and exergy analysis. The experiments took place in different days between the months of May and November of 2014. The experiment that best represented the air dehumidification and heating was selected, due to an adequate isentropic efficiency of 93%. A computational code was developed in the Engineering Equation Solver software 9.0 (ESS 9.0) for the simulation of this study. Results obtained via EES, through solution of the system of equations, were mass flow (air, condensed water), heat transfer rates, COP, entropy generation rates, irreversibility rates, and exergy variation. It was verified that the heat pump system is technically viable and provides very satisfactory results: air was heated to a temperature of 51,7 ºC and dehumidified to a 18,5% relative humidity.